Effectiveness, feasibility, and acceptability of interactive digital interventions for treatment of sexual difficulties: a systematic review, meta-analysis, and thematic analysis. - Hobbs, Lorna; Hertel, Jamie; Walton, Lisa; Schartau, Patricia; Bailey, Julia V. (Sexual & Relationship Therapy, 2026)
Sexual difficulties are common worldwide, but treatment services are scarce. Interactive digital interventions (IDIs) can deliver tailored psychotherapeutic treatment for sexual difficulties, but evidence of effectiveness, feasibility, and acceptability is needed. We conducted a systematic review across 5 databases, following PRISMA guidelines. Meta-analyses of 9 randomised controlled trials (RCTs) assessed the effectiveness of IDIs for sexual difficulties on sexual function, cognitive, emotional, and behavioural outcomes. We conducted a thematic analysis of qualitative (N = 4) and quantitative (N = 7) studies to evaluate feasibility and acceptability. IDIs improved sexual function (SMD 0.68; 95% CI 0.21–1.15), cognitive outcomes (SMD 0.62; 95% CI 0.17–1.07), emotional outcomes (SMD −0.24; 95% CI −0.48–0.00), and behavioural outcomes (SMD 0.35; 95% CI 0.11–0.59) for women (k = 6 studies). There was little data on the effects for men. Guided IDIs showed a significantly greater effect on sexual function and cognitive outcomes than self-guided IDIs. High heterogeneity and high attrition from studies limits confidence in the results. IDIs are deemed feasible and acceptable when content is relevant, inclusive, personalised, and varied. IDIs with partner involvement and therapist support are more likely to increase engagement. In summary, IDIs can be effective, feasible, and acceptable for people with sexual difficulties, and offer a promising alternative to face-to-face treatments. Lay Summary: Sexual difficulties are common and can be distressing, but access to treatment is often limited. Online sex therapy programmes can provide an alternative, more accessible treatment for sexual difficulties. We found that interactive online programmes for sex therapy can effectively treat different aspects of sexual difficulties for women. Users like online sex therapy programmes as long as the content is relevant and personalised. It is helpful to have therapist support, and if partners are involved.